The complete chloroplast genome sequence of Curcuma flaviflora (Curcuma). (2nd September 2016) - Zhang, Yan; Deng, Jiabin; Li, Yangyi; Gao, Gang; Ding, Chunbang; Zhang, Li; Zhou, Yonghong; Yang, Ruiwu
Abstract: The complete chloroplast (cp) genome of Curcuma flaviflora, a medicinal plant in Southeast Asia, was sequenced. The genome size was 160 478 bp in length, with 36.3% GC content. A pair of inverted repeats (IRs) of 26 946 bp were separated by a large single copy (LSC) of 88 008 bp and a small single copy (SSC) of 18 578 bp, respectively. The cp genome contained 132 annotated genes, including 79 protein coding genes, 30 tRNA genes, and four rRNA genes. And 19 of these genes were duplicated in inverted repeat regions.